Understanding Disaster Literacy Level in Indonesia: How can students understand natural disasters? - Dina Siti Logayah; Enok Maryani; Mamat Ruhimat; Erlina Wiyanarti (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the understanding of disaster literacy in preparing disaster-resilient students. This study used a quantitative descriptive method with a quasi-experimental design. The type of research used in this research is one group pretest-posttest. The research population is students of a public junior high school in Lembang, grade 7, for the odd semester of the 2022/2023 academic year. The research sample consisted of 33 students in class 7A. Data was collected through tests and documentation for two months, from November to December 2022. Then, the data were analyzed using descriptive statistics. Data analysis used paired t-test with the result that there was a significant difference between the pretest and posttest scores of 33 students with p 0.000. Based on these results, disaster literacy is very effective in improving disaster preparedness, especially in preparing aspects of disaster literacy knowledge, attitudes, and skills. The recommendations in this study are that only a few researchers apply disaster literacy in schools so that disaster literacy activities can become routine habits carried out by students and schools.